Returns to ICT Skills - Oliver Falck; Alexandra Heimisch; Simon Wiederhold (Center for Economic Studies and ifo Institute (CESifo), 2016)
How important is mastering information and communication technologies (ICT) in modern labor markets? We present the first evidence on this question, drawing on unique data that provide internationally comparable information on ICT skills in 19 countries. Our identification strategy relies on the idea that Internet access is important in the formation of ICT skills, and we implement instrumental-variable models that leverage exogenous variation in Internet availability across countries and across German municipalities. ICT skills are substantially rewarded in the labor market: returns are at 8 percent for a one-standard-deviation increase in ICT skills in the international analysis and are almost twice as large in Germany. Placebo estimations show that exogenous Internet availability cannot explain numeracy or literacy skills, suggesting that our identifying variation is independent of a person's general ability. Our results further suggest that the proliferation of computers complements workers in executing abstract tasks that require ICT skills.
Keywords: J31; L96; K23; 330; ICT skills; broadband; earnings; international comparisons